Beyond Awareness: Investigating the Disconnect Between Oral Health Knowledge and Caries Experience (DMF-T) in Indonesian Primary Schoolchildren - Yona Ladyventini; Suci Rahmasari; Bobby (HM Publisher, 2025)
Dental caries remains a significant public health problem among Indonesian children, impacting their quality of life and development. While oral health knowledge is considered crucial for prevention, its direct impact on caries experience, particularly in specific Indonesian contexts, requires further investigation. This study aimed to assess the relationship between oral health knowledge and caries experience (DMF-T index) among grade 2 students at an Islamic Integrated Primary School in Indonesia. A cross-sectional study was conducted involving 85 second-grade students selected via purposive sampling. Oral health knowledge was assessed using a validated, structured questionnaire covering topics like tooth brushing importance, frequency, caries causes, and prevention. Caries experience was measured using the DMF-T (decayed, missing, filled teeth) index through clinical examinations performed by trained dental personnel. Data were analyzed using descriptive statistics and the Chi-square test to determine the association between knowledge level (categorized as low or sufficient) and DMF-T status (categorized as low, moderate, or high), with significance set at p<0.05. The study included 45 (52.9%) female and 40 (47.1%) male students. The majority of students (80%, n=68) demonstrated sufficient oral health knowledge, with a mean knowledge score of 5.52 (SD=1.52) on a scale of 1-7. Despite this, the prevalence of dental caries was high, with a mean DMF-T score of 7.92 (SD=5.11). Overall, 61.2% (n=52) of students were categorized as having high DMF-T status, 18.8% (n=16) had moderate DMF-T, and 20% (n=17) had low DMF-T. The Chi-square analysis revealed no statistically significant association between the level of oral health knowledge and DMF-T status (p=0.920). High DMF-T prevalence was observed in both the low knowledge group (58.8%) and the sufficient knowledge group (61.8%). In conclusion, this study highlighted a significant disconnect between oral health knowledge and actual caries experience among primary schoolchildren in this Indonesian setting. While most students possessed sufficient knowledge, the prevalence and severity of dental caries remained alarmingly high, and knowledge level was not significantly associated with DMF-T status. These findings underscore the inadequacy of knowledge-based interventions alone and emphasize the need for comprehensive, multifaceted oral health promotion programs that address behavioral, practical, and environmental factors to effectively combat dental caries in children.